Assessment of Knowledge, Attitudes and Practice of Family Planning among Women of Reproductive Age in Northern Nigeria: A Sociological Study - Hussaini Ibn Mohammed; Aisa Isa Geidam (International Journal of Behavioral Sciences, 2026)
Family planning is a very vital element of reproductive health that enables individuals and couples to decide on how many and how far they would have their children. It is important in enhancing maternal health, child health, alleviating poverty and enhancing sustainable development. Although family planning services are available in Nigeria, their use has been low in most regions in the country especially Northern Nigeria. The paper evaluated the KAP of family planning amongst reproductive women in Northern Nigeria using the sociological approach. It was cross-sectional survey research with a sample of women aged between 15-49 years of age, which was chosen through a multistage sampling method. The structured questionnaires were used to gather the data which were analysed through descriptive statistics including frequencies and percentages. The results obtained showed that women in Northern Nigeria have a relatively high awareness towards family planning methods. Nevertheless, the real use of contraceptives is still low because of the cultural beliefs, religious factors, gender relations, fear of side effects and inadequate access to reproductive health services. The research also established that practices of family planning are highly dependent on the education level, spousal support and socio-economic status. The paper concludes by finding that to enhance the use of family planning in Northern Nigeria, it is important to implement wide-ranging initiatives which not only focus on bridging information gaps but also work on overcoming socio-cultural related issues. The education programs in the community, participation of more men, better access to health care facilities, and government intervention in this area are necessary in order to increase the adoption of family planning among women of reproductive age.
Keywords: Family Planning; Knowledge; Northern Nigeria; and attitudes; and contraception; practice; reproductive health; sociological study; women